An automatic marker for vector graphics drawing tasks - Bunn, Tristan (Department of Computer Science, 2017)
In recent years, the SVG file format has grown increasingly popular, largely due to its widespread adoption as the standard image format for vector graphics on the World Wide Web. However, vector graphics predate the modern Web, having served an important role in graphic and computer-aided design for decades prior to SVG's adoption as a web standard. Vector graphics are just as - if not more - relevant than ever today. As a result, training in vector graphics software, particularly in graphic and other creative design fields, forms an important part of the skills development necessary to enter the industry. This study explored the feasibility of a web application that can automatically mark/assess drawing tasks completed in popular vector graphics editors such as Adobe Illustrator, CorelDRAW, and Inkscape. This prototype has been developed using a collection of front-end and back-end web technologies, requiring that users need only a standards-compliant, modern web browser to submit tasks for assessment. Testing was carried out to assess how the application handled SVG markup produced by different users and vector graphics drawing software; and whether the assessment/scoring of submitted tasks was inline with that of a human marker. While some refinement is required, the application assessed six different tasks, submitted eleven times over by as many individuals, and for the greater part was successful in reporting scores in line with that of the researcher. As a prototype, serving as a proof of concept, the project proved the automatic marker a feasible concept. Exactly how marks should be assigned, for which criteria, and how much instruction should be provided are aspects for further study; along with support for curved path segments, and automatic task generation.